Study on status, Zoonoses, Biowarfare, Economic and public health importance of anthrax: Review - Daniel Tamirat Welde Mariam (International Journal of Veterinary Science and Research - Peertechz Publications, 2023)
Anthrax is a serious infectious disease caused by a bacterium called Bacillus anthracis. It can affect humans and animals, especially grazing livestock such as cattle, sheep, and goats. Anthrax spores are very resistant and can survive in the environment for a long time. People can get anthrax from direct contact with infected animals or animal products, or from inhaling or ingesting anthrax spores. There are four types of anthrax infection in humans: cutaneous, gastrointestinal, inhalation, and injection. Anthrax is also a potential bioterrorism agent, as it can be easily produced and dispersed as a powder or a liquid. Anthrax is still a neglected global health challenge that requires constant vigilance and collaboration among various stakeholders. As new technologies and strategies emerge, the current status and trends in the prophylaxis and management of anthrax disease need to be updated and evaluated regularly. The disease poses a significant public health and economic burden in the countries, especially in rural areas where livestock is the main source of livelihood. Since the disease is endemic to Ethiopia awareness of its status, economic, zoonoses, and public health significance must be addressed. Anthrax is a disease that requires constant vigilance and preparedness, as it poses a threat to both natural and deliberate outbreaks, enhancing surveillance, outbreak response, and diagnostics can help prevent and control anthrax cases in animals and humans, and reduce the social and economic consequences of this disease. Therefore, the objectives of this paper are to review the status, zoonoses, biowarfare, and economic and public health importance of anthrax.